Trusted End Host Monitors For Securing Cloud Datacenters - shieh, alan; Kandula, Srikanth; Greenberg, Albert (22nd ACM Symposium on Operating System Principles (Work-in-progress session), 2009)
Although datacenters dedicated for cloud computing services are becoming increasingly prevalent, the current datacenter network security architecture is poorly suited for this application. Policy enforcement is smeared between the network and end hosts, increasing cost and complexity while reducing flexibility and security. Enforcement is typically done at network chokepoints, which inherently see high traffic levels from aggregate traffic; packet filters and deep packet inspection engines that can operate at these data rates require expensive, custom hardware.